Integrasi Prinsip Estoppel sebagai Pelengkap Regulasi Itikad Baik dalam Hukum Perdata Indonesia - Erwin Susilo; Bagus Sujatmiko; Suhaimi Suhaimi (Jurnal Penelitian Hukum De Jure, 2026)
This study seeks to investigate the concept of estoppel and its potential incorporation into Indonesian civil law. This research is important not because Indonesian civil law lacks protection, but because the existing framework may not always provide optimal conceptual articulation in addressing losses arising from reliance. The Civil Code recognizes principles such as pacta sunt servanda and good faith; however, protection of reliance is not limited to these principles, as it is also addressed through unlawful acts (Article 1365) and the doctrine of culpa in contrahendo. Therefore, it would be overstated to claim the existence of a legal vacuum. In many legal systems, particularly in the common law tradition, estoppel has developed to address reliance, detriment, and unconscionability. In civil law systems, the protection of reliance is not contingent upon estoppel as a separate doctrine; rather, it is integrated within established legal principles. This study uses normative legal research methods, including statutory, conceptual, and comparative approaches, by examining laws, court decisions, and legal doctrines. The findings show that estoppel has evolved from a rule of evidence into a doctrine concerned with fairness. In Indonesia, similar values are reflected in good faith, rechtsverwerking, and unlawful acts, which demonstrate how these concepts align with the evolving understanding of estoppel in promoting fairness within the legal system. Accordingly, this research does not posit estoppel as a response to a legal gap but as a complementary and adaptive conceptual framework, consisting of representation, reasonable reliance, and detriment, which may be integrated through interpretation, jurisprudential development, and gradual legal refinement.